Strontium isotope data for manganese nodules, crusts and sediments from the ocean - Steven L Goldstein; R K O extquotesingleNions (PANGAEA, 2022)
Ocean clay samples associated with ferromanganese nodules and crusts have been analysed for their 143Nd/144Nd isotopes ratio. Sr was separated for isotopic analysis using conventional cation-exchange techniques with a total blank of 1-2 x 10minus-10 g Sr. For those samples leached with acetic acid (HOAC), Sr isotope data are reported for both leachates and residues when appropriate and as bulk sample analyses otherwise. Sr isotope analyses were made on the a Vacuum Generators Micromass 30 mass spectrometer using a single Ta-filament technique.